A Framework for Comparing IS Research Paradigms: How is Design Science related to Other Research Paradigms? - Venable, John (RMIT, 2013)
Research in the information systems (IS) field is complex and growing more complex, as alternative paradigms for research are introduced, grow and expand. In addition to the more traditional paradigms of positivist and interpretive research, recently interest within IS has focussed on Design Science Research (DSR). But how does DSR compare to other research paradigms? What do they have in common? Are they compatible with each other? This paper proposes a framework that can be used to compare IS research paradigms and elucidate and illuminate key differences and issues in their respective perspectives. The framework has three dimensions: (1) empirical vs non-empirical, (2) descriptive vs evaluative or normative, and (3) value-naïve vs value-aware vs value-critical. Five alternative IS research paradigms are then positioned in the framework and their differences contrasted, with particular focus on DSR and its main activities.